(untitled) (Journal of Asian Development Studies, 2025)
This study investigates how perceptions of brand control affect influencer authenticity and how perceptions of brand control shape consumers in Generation Z (Gen Z). Since influencer marketing has become increasingly important to brands, there has been concern about the naturalness of influencers amid growing brand interference. The research examines the impact of having different levels of brand control, based on content, messaging, and sponsorship disclosures, on activation of perceived authenticity of influencers. It also examines the mediating role of negative emotions in the relationship between perceptions of brand control and influencers’ avoidance among Gen Z consumers. Quantitative research was employed, with a structured online survey administered to 400 Gen Z social media users. Findings from regression analysis indicated that high brand control, as a factor, significantly decreased perceptions of influencer authenticity and elicited negative emotions, which, in turn, served as a mediator of avoidance behavior. The results have valuable implications for brands, influencers, and policymakers, who should strike a balance between branding and independence to shape credibility and trust. This study adds to the existing body of research on influence marketing by showing a deeper psychological process through which brand control influences Gen Z consumers’ behavior.